Analysis of architectural geometries affecting stress distributions of gothic flying buttresses - Kim, Richard D. Y. (Kansas State University, 2016)
The flying buttress is one of the most prominent characteristics of Gothic architecture. Understanding stress distribution from the upper vaulted nave (high vault) to the flying buttress system would contribute greatly to preservation efforts of such iconic structures. Many investigations have emphasized structural analysis of Gothic flying buttresses, but only limited research how architectural design affects load distribution throughout the Gothic members exist. The objective of this investigation was to inspire engineers and architectural preservationists to develop further research in Gothic structural analysis and restoration by increasing understanding how architectural design of flying buttresses affects the load path being transmitted from the main superstructure to the lateral force resisting system. Several flying buttress designs under similar analytical parameters were compared in order to understand how member geometries affect stress distribution. Because Gothic design is architecturally complex, finite element analysis method was used to obtain member stress distribution (regions of compressive and tensile stresses). Architectural elevation schematics of the flying buttresses of prominent Gothic cathedrals were referenced when modeling the structural members to a computer software program (RAM Elements).
Keywords: flying buttresses; stress distribution; geometrygothic